Single-use endoscopes: A narrative review - Maged Tharwat Elghannam; Moataz Hassan Hassanien; Yosry Abdelrahman Ameen; Gamal Mohammed Elattar; Ahmed Ali El Ray; Emad Abdel Wahab Turky; Mohammed Darwish El Talkawy (Society of Gastrointestinal Intervention, 2022)
The transmission of infections through gastrointestinal endoscopy is a vital issue. The main problem lies in the use of duodenoscopes due to mechanical aspects of the scope design. Even with high-level disinfection, sterilization of the scope can fail. Hence, the Food and Drug Administration has encouraged a shift to single-use endoscopes. Available options include endoscopes with single-use components (mainly single-use endcaps), fully single-use duodenoscopes (SUDs), and even those with a disposable elevator mechanism. Clinical trials revealed that both reusable and single-use scopes have the same efficacy, while single-use scopes have benefits in terms of infection control, economic considerations, and ease of reprocessing. A few drawbacks are left to be dealt with. Reusable duodenoscopes with removable/disposable endcaps are satisfactory except in specific situations where SUDs are better to use.